1989
DOI: 10.1029/ja094ia02p01508
|View full text |Cite
|
Sign up to set email alerts
|

Ghost images of auroral X ray sources observed by directional balloon‐borne detectors

Abstract: Diffusion characteristics of auroral X rays propagating through the atmosphere have been investigated by means of a Monte Carlo simulation. The results are used to estimate the defocusing effect of multiple photon scatterings on auroral X ray images detected at balloon altitudes. It is predicted that the auroral X ray image at an atmospheric depth of 6–14 g/cm2 is occasionally accompanied by a spurious ghost image in the zenith when an auroral X ray source near the zenith is viewed by a collimated detector inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In other words, the ghost image is depressed for smaller collimation and also smaller inclination angles. OGURA and KODAMA (1989) reported that the maximum spurious contribution is found for a collimator with a…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the ghost image is depressed for smaller collimation and also smaller inclination angles. OGURA and KODAMA (1989) reported that the maximum spurious contribution is found for a collimator with a…”
Section: Discussionmentioning
confidence: 99%
“…OGURA and KODAMA (1989) first pointed out the possibility of ghost images being superposed on the real image when using a directional X-ray detector at balloon altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Such spurious images vary with the collimation angle and the zenith angle of the collimation axis. Details of these interesting features are given in a separate paper (OGURA and KODAMA, 1989). image with mono-energy at depths less than 10 g/cm2 are found to be as small as 1…”
Section: Dependence Of Defocusing On Detector Specificationsmentioning
confidence: 99%
“…Although the collimation device for the balloon-born detector is effective for making the defocusing smaller, it is occasionally accompanied by a kind of spurious ghost image relevant to the defocusing, when the inclined directional telescope is used. Details of this ghost image will be reported in a separate paper (OGURA and KODAMA, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…If the field line is connected to an observation point, some of the protons can be observed. In our actual calculation, the procedure registering the coordinate of proton is inverse by referring Ogura and Kodama (1989). That is, neutrons are emitted as a= 0, and decay into protons on the Sun-Earth line, where angle a is measured from the Sun-Earth line.…”
Section: Modelmentioning
confidence: 99%